2018
DOI: 10.1111/ppe.12522
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal obesity and severe maternal morbidity: Findings from the French EPIMOMS population‐based study

Abstract: Background Maternal obesity is increasing. There is growing evidence of its effect on severe maternal morbidity. We assessed prepregnancy obesity as an independent risk factor for severe maternal morbidity by timing and cause. Methods We designed a case‐control analysis within the EPIMOMS prospective population‐based study conducted in six French regions in 2012‐2013 (182 309 women who delivered at ≥22 weeks). Cases were all women who experienced severe maternal morbidity during pregnancy to 42 days postpartum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…About 14% of the women with SMM and 11% of controls in the Siddiqui study were obese, and about 20% in both groups were overweight. 1 The authors found significant statistical associations between maternal obesity and both overall SMM (adjusted odds ratio [OR] 1.34, 95% confidence interval [CI] 1.14, 1.58) and antepartum SMM (adjusted OR 2.07, 95% CI 1.62, 2.66), but not intrapartum/ postpartum SMM. Associations between maternal obesity and antepartum SMM were statistically significant, and of higher magnitude for SMM from severe hypertensive disorders than SMM from all other conditions.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…About 14% of the women with SMM and 11% of controls in the Siddiqui study were obese, and about 20% in both groups were overweight. 1 The authors found significant statistical associations between maternal obesity and both overall SMM (adjusted odds ratio [OR] 1.34, 95% confidence interval [CI] 1.14, 1.58) and antepartum SMM (adjusted OR 2.07, 95% CI 1.62, 2.66), but not intrapartum/ postpartum SMM. Associations between maternal obesity and antepartum SMM were statistically significant, and of higher magnitude for SMM from severe hypertensive disorders than SMM from all other conditions.…”
mentioning
confidence: 99%
“…Given its increasing prevalence, serious associated conditions, and management complications in pregnancy and the postpartum period, obesity represents an important health care problem in women of reproductive age throughout the world . Significant knowledge gaps exist in the pathophysiology of obesity, its clinical manifestations in pregnancy, and its implications for management during pregnancy and delivery .…”
mentioning
confidence: 99%
See 3 more Smart Citations